Parasite metacommunity structure of Mullus argentinae Hubbs & Marini, 1933 (Actinopterygii: Mullidae) off Rio de Janeiro, Southeastern Brazil - RAQUEL O. SIMÕES; THIAGO S. CARDOSO; ALDENICE NAZARÉ PEREIRA; FABIANO PASCHOAL; JOSÉ LUIS LUQUE (Anais da Academia Brasileira de Ciências)
Abstract Mullus argentinae Hubbs & Marini, 1933 is a common demersal fish that inhabits the Brazilian and Argentinean coastal zone. A total of 200 specimens of M. argentinae were collected over the four seasons (spring, summer, autumn, and winter), from 2009 to 2011, from the littoral of the State of Rio de Janeiro, Brazil, in order to study their parasite community, including their composition and structure. The distribution pattern of the parasite species was investigated using metacommunity analysis, in addition to beta diversity calculations and their components. We investigated the influence of the seasonality (temporal factor) and host-related biological variables (body length and mass) on the occurrence and abundance of parasites throughout their hosts. A total of 12 parasite species were collected (nine endoparasites and three ectoparasites). The digenean Prosorhynchus sp. presented the highest values of abundance, intensity, and prevalence of infection. An influence of seasonality on the abundance of almost all analyzed parasite species, and on their distribution along the studied metacommunity was observed, which indicates that temporal factors may be important for the patterns of interaction of these parasites with their hosts.